Leached degradation products from beached microplastics: A potential threat to coastal dune plants. (September 2022) - Menicagli, Virginia; Balestri, Elena; Biale, Greta; Corti, Andrea; La Nasa, Jacopo; Modugno, Francesca; Castelvetro, Valter; Lardicci, Claudio
Abstract: Plants play a fundamental role in maintaining coastal dunes but also accumulate littered microplastics (MPs). Migration tests suggest that naturally weathered MPs can leach out a broader range of potentially phytotoxic chemicals than virgin MPs. Thus, assessing MPs effects on plants using beached-collected particles rather than virgin ones is critically important. Here, the effects on plants of leachates from two pools of beach-collected and virgin MPs, high-density polyethylene (HDPE) and polypropylene (PP), and their mixture, were explored combining toxicity tests and chemical analyses. Phytotoxicity of MP leachates at different dilutions was evaluated under standard laboratory conditions using test species and under environmentally realistic conditions using the dune species Thinopyrum junceum. Leachates from beached PP and HDPE adversely affected all species, and the extent of these effects varied according to polymer type, concentration, and species. Virgin MPs had weaker effects than beached ones. Several potentially phytotoxic oxidized compounds were detected in water by GC/MS analysis, and their amount estimated. Results indicate that the molecular species leaching from beached MPs - at ppm concentration levels for the individual chemical species - can inhibit plant growth, and the effects of leachates from mixtures of degraded MPs can differ from those from individual polymers, highlighting the need for further investigation of MPs consequences for coastal ecosystems. Graphical abstract: Image 1 Highlights: Leachates from beached PP and HDPE microplastics (MPs) were tested on plants. MPs released many potentially phytotoxic oxidized degradation compounds. Their amounts were determined by thermal desorption-GC-MS after SPE. Leachates from beached MPs reduced seed germination and early plant growth. Dune plants exposure to beached MPs is a potential threat to coastal ecosystems.